Context-specific approaches to the assessment of WASH exposures, interventions, and outcomes - Wolfe, Marlene. (Tufts University. Tisch Library., 2019)
Infectious diseases are a leading cause of morbidity and mortality worldwide, and there has been a worldwide increase in outbreaks and emerging infectious diseases (EIDs) since the middle of the 20th century. Water, sanitation, and hygiene (WASH) interventions have the potential to interrupt transmission of infectious diseases spread by direct or indirect contact, particularly via the fecal-oral route, and are widely used in community disease prevention and for infection prevention and control. However, WASH interventions often focus on access to services without accounting for the content of those services and the ways in which the exposure to risks, appropriate interventions, and most important health outcomes may differ in each context. The goal of this dissertation is to present five case studies developing an argument that WASH-related infectious challenges can be addressed more effectively when they are assessed with a context-specific perspective along the causal chain of disease. This process includes: 1) assessing exposure to identify sources of risk, 2) designing and implementing interventions that address key pathogens and transmission pathways, and, 3) assessing the health outcomes of greatest concern. The five projects within these three themes include one project investigating exposure to zoonotic and antimicrobial resistant pathogens on hands in India, three projects evaluating handwashing interventions used during the Ebola outbreak in 2014-2016, and one project investigating the relationship between intestinal parasitic infection and child development. Each of these chapters investigates ways in which context-specificity can be addressed and the usefulness of the information that can be gained. Results confirmed that investigations of context-specificity can provide valuable information to guide WASH activities in the field, and the projects in this dissertation present approaches to exploring this context specificity and providing richer, more contextualized information about exposures, interventions, and outcomes. This body of work demonstrates that taking this perspective can prompt valuable improvements in WASH approaches, and this research should be continued to provide more concrete recommendations for best practices against the changing landscape of infectious disease.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Civil Engineering.; Advisor: Daniele Lantagne.; Committee: Amy Pickering, Kara Nelson, and Steve Luby.; Keyword: Environmental health.